Selective Avoidance: Understanding How Position and Proportion of Online Incivility Influence News Engagement. (June 2023) - Lu, Shuning; Liang, Hai; Masullo, Gina M.
While most research has examined incivility in political contexts, few studies have explored the role of online incivility in contexts where partisan cues are lacking. Integrating insights from selective exposure, media salience, and serial position effects, we proposed the concept of "incivility salience" and examined how its two manifestations—position and proportion of uncivil messages in a comment thread—affected news engagement behavior. Through two conjoint experiments in the United States, we found that people avoided engaging with comment threads starting with uncivil content and the ones with a higher proportion of uncivil content. Furthermore, we identified that the salience of uncivil content could influence the extent to which people perceive such content as uncivil, which in turn impacts engagement behavior. Overall, this study offers a novel framework that considers incivility salience as a core element for understanding the perceptual and behavioral effects of online incivility.